Exploring pedagogical dissonance in including a traditional acupuncture treatment approach into a western biomedical evidence-based Physiotherapy curriculum - Anjos, Ana Alexandra (Department of Health and Rehabilitation Sciences, 2023)
Background: We cannot speak about complementary and alternative medicine without speaking about the most popular form of it, acupuncture, and its connection with health maintenance or forms of intervention to recover it. Over the last few years, acupuncture has been increasingly used for the treatment of pain either as a combined or complementing therapy, and evidence also suggests an increased in physiotherapists interested in acupuncture. The study aimed to 1) explore the scientific support for the combined use of acupuncture and physiotherapy in MSK conditions through a systematic review and 2) to explore the inclusion of acupuncture in undergraduate curricula as an elective course by doing a quantitative descriptive survey. Methods: Three major databases were used for the conduction of the systematic review of literature, taking place from March 2019 to May 2019, i.e., Cochrane Library, PubMed, and PEDro (Physiotherapy Evidence Database). For inclusion criteria were accepted only randomized controlled trials (RCT) published in English, released within the past decade, and using subject's adult population with MSK conditions. A quantitative descriptive survey was conducted among physiotherapists registered with professional societies in the United Arab Emirates and South Africa. A questionnaire was distributed to registered members using an online format to explore demographic information, usage of acupuncture as a treatment modality, and level of agreement for including acupuncture in undergraduate curricula. Results: Systematic Review (CHAPTER 3) The results from the electronic search yielded a total of 227 abstracts and study titles. Eight studies were considered after a detailed screening, in the included studies six of them were considered for a quantitative meta-analysis and all eight were used to perform a qualitative analysis. In total 960 patients were included, with 349 and 611 patients respectively divided into intervention and control groups. No statistically significant results were found in studies assessing pain to back up the combination of physiotherapy and acupuncture, as well in studies assessing range of motion in knee osteoarthritis. When comparing the baseline of physiotherapy combined with acupuncture or physiotherapy alone statistically significant improvements were found within-group. The studies that examined Isometric Neck-Muscle Strength (INMS) expressed noteworthy bettering within groups with physiotherapy combined with acupuncture being more viable than acupuncture or physiotherapy alone. The Constant Shoulder Assessment (CSA) for shoulder function was altogether superior within the exercise plus acupuncture group compared with the exercise group. Survey (CHAPTER 4) One hundred eighty-one physiotherapists completed the survey, with 35.4% (n=64) from the UAE, while 64.5% (n=117) were from South Africa. Additionally, 78.5% (n=142) of the participants were female, while 21.5% (n=39) were males. The mean (SD) age of the participants was 41.2 (11.9) years, and there was no statistical difference between the two countries (t=0.04, p=0.97). Thirty-five percent had a postgraduate qualification. Sixty-two (34.2%) physiotherapists reported a specialization in acupuncture, with the majority at certificate level. More physiotherapists in the UAE (57%) agreed that acupuncture ought to be included within the undergrad educational curriculum compared to South Africa (44%). Conclusion: There was no noteworthy prove found to back that the addition of acupuncture to physiotherapy treatments includes advantages to pain decrease. This review did, however, observe benefits of including acupuncture together with physiotherapy treatment in the diminishing of neck incapacity, muscle strength and shoulder function. Although physiotherapists are gaining qualification in acupuncture and using in practice, there is not sufficient traction on the inclusion of acupuncture in undergraduate curriculum.